Thermal-induced structural and optical investigations of AgZnO nanocomposite thin films. (July 2018) - Singh, S.K.; Singhal, R.
Abstract: In the present paper, we have successfully synthesized AgZnO nanocomposite thin films by RF-magnetron sputtering technique at room temperature. Systematic investigations of thermal-induced structural and optical modifications in AgZnO thin films have been observed and described. The AgZnO thin films were annealed at three different temperatures of 300 °C, 400 °C and 500 °C in vacuum to prevent the oxidation of Ag. The presence and formation of Ag nanoparticles were estimated by transmission electron microscopy. X-ray diffraction analysis revealed the structural information about the crystalline quality of ZnO. The crystallinity as well as the crystallite size of the films have been found to be improved with annealing temperatures. The estimated crystallite size was ∼15.8 nm for as-deposited film and 19.0 nm for the film at a higher temperature. The chemical composition and structural analysis of as-deposited film were carried out by X-ray photoelectron spectroscopy. A very sharp absorption band appeared at ∼540 nm for Ag NPs that is associated with the surface plasmon resonance band of Ag. A noticeable red shift of about ∼12 nm has been recorded for films annealed at 500 °C. Atomic force microscopy has been utilized to examine the surface morphology of the as-deposited and annealed films. The grain size was found to be increase with increasing annealing temperature, while no significant changes were observed in the roughness of AgZnO thin films. Raman spectroscopy revealed lattice defects and disordering in the films after the thermal annealing. Graphical abstract: Highlights: RF-sputtered AgZnO nanocomposite thin films have been successfully synthesized. Thermal-induced structural and optical modifications have been investigated. Presence of Ag nanoparticles were confirmed by transmission electron microscopy. A significant surface plasmon band shifting has been observed with thermal annealing.